The Essential HR Handbook, 10th Anniversary Edition - Armstrong, Sharon; Mitchell, Barbara (Career Press, 2019)
Since 2008, busy managers by the tens of thousands have turned to this best-selling book as a handy guide to the ins and outs of human resources. And no wonder! Because whether you're a small business owner, a manager in a business without an HR department, or even a seasoned HR professional, The Essential HR Handbook will help you handle any personnel problem-from onboarding to outplacement-quickly and easily. This fully updated 10th anniversary edition is packed with information, tools, checklists, sample forms, and timely tips to guide you through the maze of personnel issues in today's complex business environment. In it you'll find out how to: Attract talented staff through social media recruiting Identify legal pitfalls to avoid lawsuits and regulatory interference Train a diverse and inclusive multigenerational workforce Provide the compensation and benefits package that will make your organization an "employer of choice" Streamline your orientation and onboarding practices so new employees hit the ground running Whenever personnel problems arise, having The Essential HR Handbook on your bookshelf is like having a team of expert HR consultants at your beck and call!
Online resource; Title from title page (viewed January 1, 2019)
Keywords: Personnel management; Personnel Management; Personnel; Direction